Understanding the global drivers of inflation: How important are oil prices? - Jongrim Ha; M. Ayhan Kose; Franziska Ohnsorge; Hakan Yilmazkuday (Koç University-TÜSIAD Economic Research Forum (ERF), 2023)
This paper examines the global drivers of inflation in 55 countries over the 1970-2022 period. We estimate a Factor-Augmented Vector Autoregression model for each country and assess the importance of several global (demand, supply, and oil price) and domestic shocks. We report three main results. First, global shocks have explained about 26 percent of inflation variation in a typical economy. Oil price shocks accounted for only about 4 percent of inflation variation, but they had a statistically significant impact on inflation in three quarters of countries. Second, global shocks have become more important in driving inflation variation over time. The share of inflation variance caused by oil price shocks increased from 4 percent prior to 2000 to roughly 9 percent over the 2001-2022 period. They also accounted for some of the steep runup in inflation between mid-2021 and mid-2022. Finally, oil price shocks tended to contribute significantly more to inflation variation in advanced economies; countries with stronger global trade and financial linkages; commodity importers; net energy importers; countries without inflation-targeting regimes; and countries with pegged exchange rate regimes. Our headline results are robust to a wide range of exercises - including alternative measures of global factors and oil prices - and aggregation of countries.
Keywords: E31; E32; Q43; 330; Inflation; oil prices; global shock; domestic shock; FAVAR; exchange rates